The Settlement of Bad Loans and Executions on Warranty Bound by Liability - Sari, Anggi Mahendra; Witasari, Aryani (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2022)
This study aims to determine and analyze 1) How is the settlement of bad loans on guarantees tied to mortgages? PT. Bank Mandiri (Persero) Tbk Tegal Area, 2) How is the execution of Mortgage carried out at PT. Bank Mandiri (Persero) Tbk Tegal Area and. This research method uses approach empirical juridical, namely seeing the workings of law in society. The data used are primary data, namely data obtained directly from the field by conducting interviews, as well as secondary data in the form of library research. The data analysis used is a qualitative analysis which draws conclusions deductivelyf. The results of this study indicate that1) The stages carried out by PT Bank Mandiri (Persero) Tbk Tegal Area to resolve non-performing loans according to Bank Mandiri Credit Policy (KPBM) as outlined in the Standard Operating Procedures for Credit Collection and Recovery (SOP CCR), by dividing it into 3 (three) stages, namely: the peaceful settlement stage, the coaching stage, and the credit rescue stage. 2) Execution of mortgage right inPT Bank Mandiri (Persero) Tbk Tegal Area experienced several obstacles that arise, so that in practice the applicable regulations have not been effective, this is due to there is non-compliance with a rule, namely Article 11 paragraph (2) letter (j) Act No. 4 of 1996 concerning Mortgage Rights on Land and Objects Related By Land (UUHT) that is the promise that the grantor of the Mortgage will vacate the object of the Mortgage at the time of execution of the Mortgage.